Mechanical, thermal and morphological properties of woven kenaf fibre reinforced polylactic acid (PLA) composites - Mohd Nor, Mohd Azlin; Salit, Mohd Sapuan; Mohamed Yusoff, Mohd Zuhri; Zainudin, Edi Syams (Springer - Korean Fibers Society, 2022)
The growing concern over waste disposal issues of petroleum-based products has sparked the interest in using biodegradable material for composite manufacturing. Natural fibers have been proven to be excellent reinforcements for polymer composites that can mitigate the problems associated with synthetic-based composite products. The study aims to determine the mechanical, thermal, and morphological properties of biodegradable woven kenaf reinforced polylactic acid composites. The composites were developed using the hot press process. The effect of different fiber contents on the mechanical and thermal properties of the composites was examined. The results show the addition of woven kenaf has improved the tensile, flexural, and impact strength of the composites. The WK40 yielded the highest tensile, flexural, and impact strength, which recorded 61 MPa, 62 MPa, and 48 kJ/m2 respectively. However, the flexural modulus of the composites was slightly reduced by 6.7 % after the 40 % addition of woven kenaf fiber. The thermogravimetric analysis showed the WK40 sample gave the highest residue and made the composites more resistant to heat and stable. The morphological properties of the composites were analyzed using a scanning electron microscope (SEM). The SEM micrographs showed that the interfacial bonding between fiber-matrix is adequate and improved the mechanical and thermal properties of WK/PLA composites. Statistical analysis was performed using one-way ANOVA and showed significant differences between the results. In conclusion, the composites have displayed good mechanical and thermal performance at a lower manufacturing cost and have an excellent potential to be used as automotive parts.